TECHNOLOGICAL PROCESS OF PRODUCTION OF HIGHQUALITY SEAMLESS PIPES ON JSC «BMZ – MANAGEMENT COMPANY OF HOLDING «BMK» - Yu. L. Semchin; O. I. Kom (Литьë и металлургия)
The whole technological process of the high-quality seamless pipes production on the pipe-rolling unit of JSC “BMZ” is considered.